Chronic Political Instability and the HIV/AIDS Response in Guinea-Bissau from 2000 to 2015 - Galjour, Joshua (2022)
Guinea-Bissau suffers from political instability and an unusually high HIV/AIDS burden compared to other countries in the West Africa region. We conducted a systematic review on the HIV/AIDS epidemic in Guinea-Bissau during the Millennium Development Goals (MDGs) period (2000-2015), which dovetailed with a period of chronic political instability in the country's history. We searched published works on the HIV/AIDS epidemic in Guinea-Bissau for references to chronic political instability. Six databases and the grey literature were searched, informed by expert opinion and manual research through reference tracing. Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines were followed. The search yielded 122 articles about HIV/AIDS in Guinea-Bissau during the MDG years. Biomedical, clinical, or epidemiological research predominated public health research production on HIV/AIDS in Guinea-Bissau in this period. Six articles addressing themes related to chronic political instability, including how political instability has affected the HIV/AIDS disease response, were identified. The results suggest the importance of considering a broader political epidemiology that accounts for socio-political aspects such as governance, human rights, and community responses into which any national HIV/AIDS response is integrated.